The Analysis of Conditional Sentence Errors Pattern in Writing Sentences of the Eleventh Grade Students of SMA Negeri 5 Bandar Lampung - Fangky Adetia (Bandar Lampung University (UBL), 2014)
Making errors is expected to lead to some improvements in future learning. The general purpose of this research is to find out the students' errors in using conditional sentences in writing sentence.This study uses descriptive qualitative research. The data, which were retrieved from students’ conditional sentence writing. A class of eleventh grade students (Class XI IPA 3) science class of SMA N 5 Bandar Lampung. Data analysis discovered that most of the students still made all of the four error types under the heading of surface strategy taxonomy.The error types that were identified in the students’ conditional sentence writing were ranked for the surface strategy taxonomy, errors in misformation amount to 166 errors (54.07%), omission 74 errors (28.46%), addition 18 errors (6.94%), and misordering only 1 errors (0.38%). For each type of the conditional, type one got omission 46 errors (17,76%), misformation 19 errors (7.33%), addition 7 errors (2.7%), misorderin 1 error (0.38%), on type two got misformation 62 errors (23.93%), addition 11 errors (4.24%), and omission 10 errors(3.86%), on type three misformation 85 errors (32.81%), and omission 18 errors(6.94%). These figures suggest that teachers should take necessary instructional steps (for example through a series of extensive and intensive practices on grammar) as a follow-up to improve students’ grammar competence, without leaving the importance of spontaneity and overall meaning in writing.